Tunable Q-Switched Fiber Laser Based on a Graphene Saturable Absorber Without Additional Tuning Element - Renli Zhang; Jun Wang; Meisong Liao; Xia Li; Pei-Wen Kuan; Yinyao Liu; Yan Zhou; Weiqing Gao (IEEE Photonics Journal)
A tunable passively Q-switched fiber laser is fabricated using a graphene saturable absorber. The graphene saturable absorber is composed of a tapered fiber coated with graphene nanosheets. It combines the abilities of a saturable absorber and power-dependent tunable filter, thereby simplifying the structure of the tunable passively Q-switched fiber laser. The transmission peak of the graphene saturable absorber is linearly dependent on the input power and temperature, with slopes of approximately −0.35 nm/mW and −3.63 nm/°C, respectively. The Q-switched fiber laser exhibits a tunable wavelength range of 7 nm (from 1558 to 1565 nm). The output pulse offers the shortest pulse duration of 2.22 μs with a repetition rate of 39.1 kHz and the widest pulse duration is 5.9 μs that corresponds to a repetition rate of 21.3 kHz. The maximum pulse energy is 251.9 nJ, corresponding to an average output power of 8.6 mW.